MENELISIK KEBERHASILAN KEPEMIMPINAN HAMBA DALAM PENGGEMBALAAN BERDASARKAN SURAT-SURAT PENGGEMBALAAN - Herika, Herika; Gidion, Gidion; Manik, Disetra Fiser (P3M STT Kristus Alfa Omega, 2022)
This study focuses on researching and formulating material on servant leadership in the pastoral letter which is the key to success in leading the pastor of the congregation. The method used is a qualitative method. Based on studies conducted by researchers. The material ideas found through the exposition of the three letters are divided into four broad outlines, namely, material on the spiritual growth of leaders, material on servant leaders' attitudes, congregational teaching skills, and pastoral managerial abilities.